2017
DOI: 10.3339/jkspn.2017.21.2.75
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Infection in Pediatric Renal Transplant Recipients: A Single Center Experience

Abstract: To investigate the frequency, presentation, management, and outcome of cytomegalovirus (CMV) infection in pediatric patients who underwent renal transplantation. Methods: We performed a retrospective chart review of 70 patients under the age of 18, who underwent renal transplantation between January 1990 and November 2014. A diagnosis of CMV infection was based on serology, molecular assays, antigenemia assays, and culture. CMV infection was defined as detection of virus and CMV disease was diagnosed when clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Cytomegalovirus has been reported as the most common opportunistic viral infection following renal transplantation and is associated with increased morbidity, mortality, and graft dysfunction and loss. Fever, malaise, gastritis, enteritis, hepatitis, leukopenia, thrombocytopenia, and pneumonia are some of the clinical features of CMV disease . Increased incidence of CMV infection is seen with CMV‐positive donation to CMV naïve recipients …”
Section: Discussionmentioning
confidence: 99%
“…Cytomegalovirus has been reported as the most common opportunistic viral infection following renal transplantation and is associated with increased morbidity, mortality, and graft dysfunction and loss. Fever, malaise, gastritis, enteritis, hepatitis, leukopenia, thrombocytopenia, and pneumonia are some of the clinical features of CMV disease . Increased incidence of CMV infection is seen with CMV‐positive donation to CMV naïve recipients …”
Section: Discussionmentioning
confidence: 99%
“…In two studies conducted in pediatric patients, the median age at the time of kidney transplantation was 12 20 and 13 years. 6 In the 38 studies that reported the sex distribution of SOT recipients, males accounted for 43.3%-85.5% (Table S9). Distribution of patients according to CMV serostatus was documented in less than half of the retained studies (n = 23 studies, 46.9%).…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Most studies on the rate of CMV disease in SOT recipients (n = 21/23, 91.3%) reported an incidence ranging between 0% and 19.0%, with results uniformly distributed within the range. [6][7]9,20,25,[30][31][32][33][34]36,37,[42][43][44][45][46][47][48][49][50] Based on five studies, all conducted in kidney recipients, CMV disease occurred within 4-6 months posttransplantation. 7,9,20,44,46 According to Table 1, rates of CMV disease were consistent across the countries of interest except for China, 49 Colombia, 30 South Korea, 25 and Turkey, 47 where rates were lower.…”
Section: F I G U R Ementioning
confidence: 99%
See 2 more Smart Citations